STRATEGI KAMPANYE KEMENANGAN WALIKOTA BEKASI RAHMAT EFFENDI DALAM PILKADA KOTA BEKASI - Azhar Hadi Pratama (2023)
This study aims to explain how the political campaign strategy carried out by Bekasi Mayor Rahmat Effendi when he ran for the Regional Head Election (PILKADA) in Bekasi City. The method used in this research is descriptive qualitative using primary and secondary data sources. In this study the authors used data collection techniques through interviews and literature study. In-depth interviews are a technique carried out by both parties, namely the interviewer who asks the questions and the resource person/informant who provides answers to the questions in the research (Moleong, 2006: 186). The final results of this study show that Rahmat Effendi as an incumbent who attracts a lot of voters' attention, the program and work ability of an actor are very influential in building the personal image of a regional leader candidate. Good performance and performance by the campaign team also influenced Rahmat Effendi's victory. Capitalizing on the candidate's personality, of course the campaign team tries to avoid taking sides in order to gain the people's support and most importantly seek sympathy for non-supporters, in an effort to develop support from the public. The Political Campaign and Political Communications carried out by Rahmat Effendi can be said to have succeeded in attracting votes from the people of Bekasi city by obtaining 336,900 thousand votes in the 2013 Bekasi City election and in the 2018 Bekasi City election obtaining 697,630 thousand votes.